Analysis Of Community Clean Water Demand In Kotawringin Timur District - Norhayati Norhayati (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2022)
This study aims to determine how income, population, price and water quality influence the demand for clean water in East Kotawaringin Regency. The research method used in this study is a descriptive-quantitative approach. The analysis unit for this research is the people of Ketapang, Mentaya Hilir Utara, Kota Besi, Baamang and Cempaga sub-districts. East Kotawaringin Regency which made a request for clean water with a total of 154 respondents and purposive sampling. This study uses primary data obtained directly by researchers with observation techniques, interviews, distribution of questionnaires and literature searches. The collected data were analyzed using multiple linear regression analysis and descriptive analysis, the software used was SPSS 25. The results of this study concluded that income and population had a positive and significant influence on the level of demand for clean water. Meanwhile, the price and quality of water have a positive and insignificant influence on the level of demand for clean water. Simultaneously, the variables of income, population, price and water quality have a significant influence on the demand for clean water in East Kotawaringin Regency.